A conceptual framework on constructing effective learning content for programming novices - Ling Chean, Swee; Ban Ho, Sin; Chai, Ian (International Journal of Engineering and Technology, 2018)
An e-learning system provides a platform for communication between the educators and the students. It facilitates the sharing of information and learning content in a form, which can be easily accessed by the users. In e-learning educational systems, a learning content management system (LCMS) is commonly used for developing and managing learning content. An overly comprehensive LCMS might not suit the needs for all domains such as learning programming for novice learners. Teaching novice programming learners is not an easy task as mentioned in many studies. Complicated explanations and boring teaching methods cause loss of interest in learning programming. Many educational studies have been carried out with different aspects and approaches to improve teaching and learning programming in school and tertiary levels of study. This paper proposes a conceptual framework for constructing effective learning content. It is challenging for Malaysian educators to design and prepare learning content that allows programming novices to learn at their own pace and skill levels. It is believed that an effective learning content framework would benefit educators who intend to start teaching programming to novices.Â